The Comparison Of Chicken Farming Business On Various Patterns In North Bengkulu Regency - Harianto Harianto; Nyayu Neti Arianti; Putri Suci Asriani (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2019)
This study aims to calculate and compare the income and the level of efficiency of poultry farming with various business patterns, namely